Millennial Leadership and the Quality of Work Environment in Travel and Tourism Industry - Alexander Patrick Pantoro; Munawaroh Munawaroh (Directorate of Academic Research and Community Services, 2022)
This study holds purpose to find out which leadership is adapted by millennial leaders with the usage of traits leadership, behavioral leadership, and contingency leadership. Furthermore, this paper also investigates how millennial leaders affect the work environment in physical, psychological, and social form. Lastly, the other aim of this research is to discover whether millennial leaders approves as a good strategic plan in improving the quality of work environment. Qualitative methods such as literature review and in-depth interviews were used to measure the connection between two variables. The contradictive result from this research suggests that millennial leaders do influence their work environment by their performance, open-mindedness, communication skill, and willingness to listen and learn to enhance the quality of work environment.